Decoding the court legal data insights from the Supreme Court of Canada - Alschner, Wolfgang; MacDonnell, Vanessa; Mathen, Carissima (Routledge, 2024)
"This edited collection combines state-of-the-art legal data analytics with in-depth doctrinal analysis to study the Supreme Court of Canada (SCC), Canada's top court. A data analytics perspective adds new dimensions to the study of courts and their case law. It renders legal analysis scalable, making it possible to investigate thousands of judicial decisions, adding new breadth and depth. It also enables researchers to combine doctrinal questions about how the law evolves with institutional questions about how courts operate, shedding new light on how law works in practice. By applying a range of methods to study the content of SCC decisions, this work bridges the gap between qualitative and quantitative research. Demonstrating how new analytical perspectives can generate new insights about the Supreme Court, an institution which is closely studied by scholars both within and outside Canada, the book will be essential reading for legal scholars and political scientists, particularly those working in public law and in empirical legal studies"
Includes bibliographical references and index.
Keywords: Canada. -- Supreme Court.; Separation of powers -- Canada.; Judicial process -- Canada.; Justice, Administration of -- Canada.; Courts -- Canada.; Séparation des pouvoirs -- Canada.; Processus judiciaire -- Canada.; Tribunaux -- Canada.; LAW / General; LAW / Comparative; LAW / Constitutional